Shape effect of piezoelectric energy harvester on vibration power generation - Basari, Amat Amir; Sosuke, Awaji; Song, Wang; Seiji, Hashimoto; Shunji , Kumagai; Kenji, Suto; Hiroaki, Okada; Hideki, Okuno; Bunji, Homma; Wei, Jiang; Shuren, Wang (Scientific Research Publishing Inc., 2014)
Vibration energy harvesting is widely recognized as the useful technology for saving energy. The piezoelectric energy harvesting device is one of energy harvester and is used to operate certain types of MEMS devices. Various factors influence the energy regeneration efficiency of the lead zirconate titanate piezoelectric (PZT) devices in converting the mechanical vibration energy to the electrical energy. This paper presents the analytical and experimental evaluation of energy regeneration efficiency of PZT devices through impedance matching method and drop-weight experiments to different shape of PZT devices. The results show that the impedance matching method has increased the energy regeneration efficiency while triangular shape of PZT device produce a stable efficiency in the energy regeneration. Besides that, it becomes clear that the power, energy and subsequently efficiency of the triangular plate are higher than those of the rectangular plate under the condition of the matching impedance and the same PZT area.